Website Estância e Forte Santa Tecla – patrimônio, educação e turismo - Pinheiro, Ivan Cesar dos Santos (2019)
The present work deals with the creation of the website www.fortesantatecla.wixsite.com/inicio to store documents, academic and didactic materials, maps and other tools that facilitate the free access and research of the history of the farm and fort of Santa Tecla and its context, which involves a possible Jesuit silo or lime source, a context that is located in the municipality of Bagé-RS, facilitating its recognition as patrimony, education and tourism. Research was also carried out in order to describe aspects of the history and structure of the farma, outpost of São Miguel das Missões, and fort, recovering the history and memory of the archaeological site and the material that was found there and what is still there we have also sought to understand, systematize and look at issues that have remained open for more than a century among researchers in the region, through the analysis of historical documentation and research in the area.